2008
DOI: 10.1002/cncr.23375
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic cell transplantation‐comorbidity index and Karnofsky performance status are independent predictors of morbidity and mortality after allogeneic nonmyeloablative hematopoietic cell transplantation

Abstract: BACKGROUND Elderly and medically infirm cancer patients are increasingly offered allogeneic nonmyeloablative hematopoietic cell transplantation (HCT). A better understanding of the impact of health status on HCT outcomes is warranted. Herein, a recently developed HCT‐specific comorbidity index (HCT‐CI) was compared with a widely acceptable measure of health status, the Karnofsky performance status (KPS). METHODS The outcomes of 341 patients were evaluated, conditioned for either related or unrelated HCT by 2‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
170
4
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(192 citation statements)
references
References 77 publications
14
170
4
4
Order By: Relevance
“…We found that a higher cut-off value of the PAM score (> 24 vs. 24) was better for predicting the prognosis than the original cut-off value (>23 vs 23). In the present study, NRM was relatively low compared with past reports [9][10][11][12][14][15][16]. NRM in the previous reports which could not show utility of HCT-CI was also relatively low [14][15][16].…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…We found that a higher cut-off value of the PAM score (> 24 vs. 24) was better for predicting the prognosis than the original cut-off value (>23 vs 23). In the present study, NRM was relatively low compared with past reports [9][10][11][12][14][15][16]. NRM in the previous reports which could not show utility of HCT-CI was also relatively low [14][15][16].…”
Section: Discussioncontrasting
confidence: 83%
“…The rates of patients with HCT-CI > 2 and > 3 were 52.6% and 24.4% in the present study, respectively. The rates of patients with HCT-CI > 2 and > 3 were 32-76% and 20-50% in previous reports about HCT-CI in patients with RIC regimen [9][10][11][12][14][15][16], respectively. Although the rate of patients with HCT-CI > 2 in the present study was comparable to patients in the previous reports, the rate of patients with HCT-CI > 3 was relatively low compared with previous reports.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The EBMT risk score 5 is a well-known tool that predicts the risk of death after allo-HCT using a score based on age, disease stage, time interval from diagnosis to transplant, donor type and donor-recipient gender combination. Prognostic validity has also been demonstrated by the clinician-assessed Karnofsky Performance Score and by the co-morbidity score by Sorror et al 6,7 A recently published pilot study by Wood et al suggests that cardiopulmonary fitness, as defined by either peak oxygen uptake or the 6-minute walk distance Test (6-MWD), is a predictor of symptom severity, quality of life, and mortality in patients undergoing allo-HCT. 8 The risk of mortality post-procedure was substantially higher in patients whose pre-procedure VO 2peak was 16 ml/kg/min compared with those with a VO 2peak >16 ml/kg/min (hazard ratio of 6.7).…”
mentioning
confidence: 97%